Divalent metal modulation of Japanese flounder (Paralichthys olivaceus) purinergic P2X7 receptor. Issue 3 (23rd January 2018) - Paredes, Carolina; Li, Shuo; Chen, Xiaoli; Coddou, Claudio
Abstract : Paralichthys olivaceus P2X7 receptor (poP2X7R) is a recently identified as a P2X7 purinergic receptor involved in innate immunity of the Japanese flounder Paralichthys olivaceus . Divalent metals are allosteric modulators of mammalian P2XRs, but there is no information for fish P2XRs. Here, we characterized the effects of divalent metals on poP2X7R channel activity by electrophysiology and molecular biology techniques. Copper, zinc and mercury inhibited poP2X7R‐mediated currents with different maximal inhibition potency, while cadmium had no effect on poP2X7R activity. Mercury‐induced inhibition was irreversible, but the inhibitory effects of copper and zinc were reversed after washout. Cooper and zinc also reduced poP2X7R‐mediated interleukin‐1 mRNA production. These findings suggest that divalent metals have potential effects on the Japanese flounder innate immune response through modulation of poP2X7R activity. Abstract : Here, we characterized the effects of divalent metals on the activity of Paralichthys olivaceus P2X7 receptor (poP2X7R), a purinergic receptor cloned from the Japanese flounder. Although poP2X7R was more resistant to metal inhibition than its human and rat counterparts, Cu 2+, Hg 2+ and Zn 2+ inhibited its channel activity and Cu 2+ prevented the poP2X7R‐mediated increase in interleukin 1 beta expression in P. olivaceus immune cells, highlighting the role of poP2X7R in the fish innate immune response.